The Influence of Job Satisfaction and Work-Life Balance on the Performance of Married Female Employees - Muhammad Prasetyo Wibowo (International Journal of Enterprise Modelling, 2026)
The increasing participation of women in the workforce has created new challenges for married female employees in balancing professional responsibilities and family obligations. This study aims to analyze the effect of work-life balance and job satisfaction on the performance of married female employees at PT.X, a household appliance manufacturing company in Medan. A quantitative research approach was employed using a saturated sampling technique involving 87 married female employees as respondents. Data were collected through questionnaires, interviews, documentation studies, and literature reviews. The data analysis technique used was multiple linear regression analysis with the assistance of SPSS version 20.0, including validity, reliability, normality, partial t-test, and simultaneous F-test analyses. The results indicate that job satisfaction has a positive and significant effect on employee performance with a t-value of 3.001 and a significance level of 0.004. Furthermore, work-life balance was found to have a stronger positive and significant influence on employee performance with a t-value of 4.923 and a significance value of 0.000. Simultaneously, job satisfaction and work-life balance significantly affect employee performance, as evidenced by an F-value of 30.942 with a significance level of 0.000. The findings suggest that organizations need to develop supportive policies related to employee welfare, fair compensation, and work-life balance to improve the performance of married female employees. This study contributes to the human resource management literature by highlighting the importance of balancing work and personal life in enhancing employee performance, particularly among women with dual roles in the workplace and family.